Climate change and global health [ - Butler, Colin D. (CABI, 2014)
"There is increasing understanding, globally, that climate change will have profound and mostly harmful effects on human health. This authoritative book brings together international experts to describe both direct (such as heat waves) and indirect (suc as vector-borne disease incidence) impacts of climate change, set in a broad, international, economic, political and environmental context. This unique book also expands on these issues to address a third category of potential longer-term impacts on global health: famine, population dislocation, and conflict. This lively yet scholarly resource explores these issues fully, linking them to health in urban and rural settings in developed and developing countries. The book finishes with a practical discussion of action that health professionals can yet take"--Provided by publisher